Research Status and Prospect of the Application of Radionuclides in Agricultural Resources and Environment - Juan ZHANG; Jinhao GAO; Xiaojun LIU; Jianfeng ZHANG; Juncheng YANG (Journal of Isotopes)
Radionuclides with a diverse range of applications and high analytical efficiency to promote multidisciplinary Innovation and developments, which are considered to be an essential tool in the field of modern science and engineering. To gain a deeper understanding of the current state of research on the application of radioactive isotopes technology in agricultural-related fields in recent years，this paper focuses on its research progress in radiation-induced mutagenesis breeding for plants，plant protection，soil and water conservation, both domestically and internationally. It mainly introduces the applications of radioactive isotopes in crop breeding and pest control, tracer technologies for the migration of nutrient elements of nitrogen and phosphorus at soil-plant-microorganism interfaces and at soil-water interfaces to prevent soil erosion, as well as the intelligent analysis of radioactive nuclides. Based on the current challenges faced by radionuclide technology in this field, along with the development of modern mass spectrometry technology, the research and development of new radioactive isotopes, and the challenges and opportunities brought by interdisciplinary integration, this paper presents prospects for the future development and application of radionuclide technology.